KAJIAN KERUSAKAN SUMBERDAYA HUTAN AKIBAT KEGIATAN PERTAMBANGAN - ARDHANA, I PUTU GEDE (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 6 No 2 (2011), 2011)
The study was conducted in order to assess the damages of forest resources due to mining activities. The method which use in this article is the nonnative legal research concerning with the legislation approach, the case study approach and the library approach. The result of this study indicated that be damage of forestry by mining activities threatens convenient ecosystem of Indonesia seriously. The study materials show obtained that the original forest area in Indonesia were 144 million hectares, but have been systematically shrinkaged that remained only 130 million hectares now, even though the 42 million hectares were completely without vegetation. Primary forest left only 43 million hectares from forest encroachment and as rate currently reaches 1.1 million hectares per year. The result study showed that according with the governor's report in 10 provincies throughout Indonesia the forest destructions are dominated by mining activities. The facts in the fields also showed that the mining locations clearly faced visiable forests of Indonesia destroyed by quarrying, waste disposal and mining operations support activities. The governmental policies to allow mining activities in protective and conservation forest will destruct of forest resources. To address the threat of forest destruction it is suggested that the Government shall revitalize the implementation of provisions with Act No. 41 of 1999, the Act No. 19 of 2004 and the Presidential Decree. No. 41 of 2004, the Cabinet Act 24 of 2010 and the Presidential Decree No. 28 of 2011 concerning with the preservation of forest resources are still maintained.
Keywords: forest damage, mining activities, the revitalization of the legislation, forest conservation